2011
DOI: 10.4161/auto.7.9.16521
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy protects breast cancer cells from epirubicin-induced apoptosis and facilitates epirubicin-resistance development

Abstract: (2011) Autophagy protects breast cancer cells from epirubicin-induced apoptosis and facilitates epirubicin-resistance development,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
144
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(155 citation statements)
references
References 38 publications
10
144
0
1
Order By: Relevance
“…The DNA synthesis inhibitor epirubicin eliminates cancer cells mainly via inducing G2/M arrest and apoptosis (39,40). The results of the present study demonstrated that, in epirubicin treated HepG2 cells, significant upregulation of the mRNA expression levels of cell cycle progression inhibitor, p21waf1/cip1, and pro-apoptosis Bax was detected (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…The DNA synthesis inhibitor epirubicin eliminates cancer cells mainly via inducing G2/M arrest and apoptosis (39,40). The results of the present study demonstrated that, in epirubicin treated HepG2 cells, significant upregulation of the mRNA expression levels of cell cycle progression inhibitor, p21waf1/cip1, and pro-apoptosis Bax was detected (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…Autophagy has also been implicated in the development of trastuzumab resistance in human epidermal growth factor receptor 2-positive breast cancer (30). A number of chemotherapeutic agents (anthracyclines and taxanes) are able to induce autophagy, and inhibition of autophagy increases drug toxicity via the induction of apoptosis in breast cancer cells (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is a highly conserved cellular degradation process that eliminates aggregated or unfolded/misfolded proteins and damaged organelles in response to stress or nutrient deprivation (17)(18)(19). It was shown that autophagy provided protection for breast cancer cells against epirubicin, an anthracycline drug used for chemotherapy, and inhibition of autophagy resensitized the MCF-7 cells to epirubicin (20). Moreover, accumulative studies imply that the UPR may involve the induction of autophagy under cellular stress (21)(22)(23)(24).…”
mentioning
confidence: 99%